Identification of terminal heat-tolerant and foliar disease-resistant fortified genotypes in wheat (Triticum aestivum L.) - Rounak Kumar; Chandra Shekhar Azad; Tirthartha Chattopadhyay; Pradeep Kumar Bhati; Om Prakash Gangwar; Subodh Kumar; Pramod Prasad; Deepak Baranwal (Cereal Research Communications, 2024)

Genetic and genomic approaches for breeding rust resistance in wheat - Deepak Baranwal (Euphytica, 2022)
Wheat rusts are considered major biotic stresses due to immense yield losses incurred by the rust pathogens. Continuous incursions and evolution among populations of rust pathogen have challenged several resistance genes deployed in wheat mega-varieties. A substantial amount of wheat production is being saved by rust resistance wheat varieties. Breeding for rust resistance aimed to transfer potential genes in wheat elite lines and discover novel alleles to diversify resistance gene stock for future wheat breeding. This class of research was initiated worldwide after the discovery of mendelian genetics. Over a century, several genetic and genomic approaches were discovered and subsequently applied in wheat research to better understand the nature of rust pathogens and accordingly deployed major and minor rust resistant genes in combination in wheat varieties. Over 240 rust resistance genes have been catalogued and several alleles/QTL have been reported. Various statistical tools and consensus maps have been designed to precisely allocate novel alleles, as well as known genes on the wheat physical map. With the advancement in genomics and next generation sequencing (NGS) technology, more than 20 rust resistance genes have been cloned in the last two decades. The mutational genomics approach was found competitive and parallel to modern NGS technology in isolating rust resistance loci. In this review, evolutionary trends of rust pathogens, source of rust resistance genes, methodology used in genetic and association mapping studies and available cutting-edge techniques to isolate disease resistance genes have been summarised and discussed.

Identification of genomic regions conferring rust resistance and enhanced mineral accumulation in a HarvestPlus Association Mapping Panel of wheat - Deepak Baranwal; Suong Cu; James Stangoulis; Richard Trethowan; Harbans Bariana; Urmil Bansal (Theoretical and Applied Genetics, 2022)